The Influence of Density on the Mechanical Response of Reinforced High-Density Polyurethane Foams: A Statistical Approach - Kerche, Eduardo Fischer; da Cruz, Joziel Aparecido; Amico, Sandro Campos (Journal of Research Updates in Polymer Science, 2022)
In this work, rigid polyurethane foams (RPUF) reinforced by micro fibrillated cellulose (MFC) were manufactured using the free rising method and also under confinement inside a closed mould, aiming to increase apparent density and improve mechanical response. Neat RPUF were also manufactured for comparison. The mechanical response, evaluated by compression (following ASTM D1621 standard) tests were correlated with the final composite apparent density (evaluated following ASTM D1622 standard). Simple linear regression statistical models, based on F-test, were developed using stat graphics software, aiming to understand and correlate the increment in density and its influence on the improvement in mechanical response. Different models were developed to describe the foam behavior. The main results show a more significant influence of the density on strength than stiffness for the neat RPUF, unlike the MFC-reinforced RPUF, which presented an opposite response. These effects could be caused by the lower content of voids when the foams were produced under confinement, and by the greater crosslink density, when MFC was added.